THE IMPORTANCE OF SOFT TISSUE SURGICAL INTERVENTIONS ON THE DISTAL PART OF THE FOOT IN THE TREATMENT OF HALLUX VALGUS - Sovilj, Mirko (Medicinski podmladak, 2023)
Since pathological anatomical changes in the distal soft tissues of the front part of the foot in hallux valgus deformity are degenerative in nature and more pronounced than changes in the bony structures, interventions on ligamentous, capsular and tendinous structures are an indispensable part of its surgical treatment. A consensus has not been established regarding the nature and method of performing distal soft tissue interventions. In order to avoid the risk of consequent aseptic necrosis of the first metatarsal bone head in case of simultaneous osteotomy at its distal level, it is necessary that the osteotomy be performed in a safe place and the plantar and dorsal segments of this capsule must remain preserved. In order to avoid the occurrence of iatrogenic hallux varus deformity, it is necessary that lateral sesamophalangeal ligament, lateral sesamoid and associated part of the plantar aponeurosis remain preserved. In order to avoid occurrence of iatrogenic hallux varus deformity, it is necessary that lateral sesamophalangeal ligament, lateral sesamoid and the associated part of the plantar aponeurosis remain preserved. Since the deep transverse metatarsal ligament keeps the sesamoid apparatus in the anatomical position, its release should be avoided. Lateral release of adductor tendons of the thumb, lateral collateral ligament and associated part of the capsule facilitate  correction of the position of the thumb with a modest contribution to the overall correction of deformity and allow access to the shortened lateral metatarsosesamoid ligament, which must be completely released, making the greatest contribution to overall correction. At the same time, mentioned interventions are safe from the aspect of risk of possible complications, especially when performed using a special dorsal intermetatarsal approach. Reconstructive interventions on the soft tissues of  medial side of the metatarsophalangeal joint of the thumb include their tightening while stabilizing the thumb in a neutral position.
Keywords: hallux valgus, distal soft tissue interventions